A comparative history of insurance law in Europe : a research agenda - Hellwege, Phillip, 1971- (Comparative studies in the history of insurance law, 2018)
The history of insurance law has fallen into neglect. It is only recently that the topic has again received attention from legal historians. However, the state of research is still unsatisfactory. Foremost, there are distinct national narratives of insurance (legal) history. And these narratives give the impression of insurance (law) being developed differently in the single European countries. The present volume works out a research agenda for a comparative history of insurance law in Europe. For that purpose the contributions to this volume present the state of research in different European countries and identify possible points of interactions between the national developments of insurance law. Future research will focus on these points of interactions. The present volume is, thus, the starting point and framework for future research in the history of insurance law in Europe.